2006
DOI: 10.5194/angeo-24-851-2006
|View full text |Cite
|
Sign up to set email alerts
|

A study of the ionogram derived effective scale height around the ionospheric <I>hm</I>F2

Abstract: Abstract. The diurnal, seasonal, and solar activity variations of the ionogram derived scale height around the ionospheric F-layer peak (H m) are statistically analyzed at Wuhan (114.4 • E, 30.6 • N) and the yearly variations of H m are also investigated for Wuhan and 12 other stations where H m data are available. H m, as a measure of the slope of the topside electron number density profiles, is calculated from the bottomside electron density profiles derived from vertical sounding ionograms using the UMLCAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
45
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 30 publications
13
45
4
Order By: Relevance
“…Therefore, the Hm variation near the dip equator would be also affected by the vertical E×B velocity. Moreover, the r values in this study are larger than those in Liu et al (2006) and Zhang et al (2006). This suggests that dependence of Hm on hmF2 is more obvious near the dip equator than at low-latitudes.…”
Section: Correlations Of Hm With Fof2 Hmf2 and B0contrasting
confidence: 65%
See 2 more Smart Citations
“…Therefore, the Hm variation near the dip equator would be also affected by the vertical E×B velocity. Moreover, the r values in this study are larger than those in Liu et al (2006) and Zhang et al (2006). This suggests that dependence of Hm on hmF2 is more obvious near the dip equator than at low-latitudes.…”
Section: Correlations Of Hm With Fof2 Hmf2 and B0contrasting
confidence: 65%
“…These results near the dip equator are not the totally same as those observed at other latitudes. At low-latitude, Liu et al (2006) showed that a weak negative or poor correlation exists between Hm and foF2 at Wuhan (30.6 • N, 114.4 • E). The poor correlation was also found Zhang et al (2006) using data from the low-latitude station, Hainan (19.4 • N, 109.0 • E).…”
Section: Correlations Of Hm With Fof2 Hmf2 and B0mentioning
confidence: 95%
See 1 more Smart Citation
“…With measurements from incoherent scatter radar, digisonde, topside sounder, and radio occultation techniques, the plasma scale heights around the F peak and the topside ionosphere are found to become larger at higher solar activity (Kutiev et al, 2006;Lei et al, 2005;Liu et al, 2006aLiu et al, , 2007aStankov and Jakowski, 2006), which will also increase plasma density at the DMSP altitude as a key role by further decreasing the reduced height z in Eq. (1).…”
Section: Discussionmentioning
confidence: 99%
“…They found that H m over Millstone Hill is overestimated by the IRI2001 model (Bilitza, 2001) and the temporal variations of H m can be explained in terms of those in the slab thickness. Liu et al (2006) reported that a moderate positive correlation is found between H m and the F 2 layer peak height (h m F 2 ) and a strong correlation between the bottomside thickness parameter B 0 and H m . A common feature is found at 13 global stations; that is, the values of H m are highest in summer and lowest in winter during daytime.…”
Section: Introductionmentioning
confidence: 99%